Core-shell microstructured nanocomposites optimized based on Box–Behnken design for enhanced suppression of hydrogen co-flow flames. (23rd March 2021) - Tianwei, Zhang; Xiangchen, Liu; Guofeng, Wang; Hao, Liu; Lei, Xiao; Yihao, Zhou; Qiang, Liang; Cunwei, Zhang
Abstract: Combustion characteristics of hydrogen-containing syngas are distinct from those of traditional hydrocarbon fuels. However, the efficiency for any fire extinguishant on syngas/air flame suppression has not been validated up to now. In this study, we developed novel core-shell microstructured nanocomposites (CSMNs) with inner seawater for syngas/air fire extinguishing. To optimize the preparation conditions, we adopted a three-factor three-level Box-Behnken design (BBD). The corrosion rate and minimum extinguishing concentration of CSMNs were determined by corrosion tests and Cup-burner experiments, respectively. Results showed that the BBD method exhibits good agreement between experimental data and fitted models. By applying numerical optimization, we determined that solid mass fraction, rotation speed, and rotation time in a range of 2–10%, 4000–8000 rpm, and 60–180 s, respectively, are the optimal preparation conditions for the CSMN preparation. The degree of corrosion rate and mass concentration in co-flow gaseous fuel/air fire suppression were reduced by more than 50% compared to an aqueous seawater solution. The updated methods can be used to study the fire inhibition efficiency of the emerging class of composite materials with the core-shell structure. This does not only provide solutions for syngas/air flame inhibition, but it also gives new insight into the application of seawater for fire extinguishment. Highlights: A new type of hydrogen fire extinguishant with core-shell structure was prepared. A Box-Behnken design method was used to optimize preparation conditions. The MEC of the novel fire extinguishant was measured by Cup-burner method. Anti-corrosion effects of outer solid materials were confirmed.